Electronic publishing : desktop publishing - Mostafa, Joshua (New York : Dorling Kindersley, 2000)
1. Desktop publishing industry - ---United States - ---Management.
Includes index.
Faculty
Keywords: Microsoft Publisher; Desktop publishing